ANALYSIS OF BIOMEDICAL PHYSICS IN PULSE OXIMETERS: PRINCIPLES OF PHOTOPLETHYSMOGRAPHY, PHOTOELECTRIC SENSORS, AND SIGNAL PROCESSING - Cahya Maulana (Khamdan Karya Cipta, 2026)
Pulse oximeter is a non-invasive biomedical device widely used to monitor arterial oxygen saturation (SpO₂) and pulse rate in clinical and ambulatory settings. This article presents a comprehensive review of the biomedical physics underlying pulse oximeter technology, emphasizing the integration of optical physics, electronic instrumentation, and digital signal processing. The discussion covers the principles of photoplethysmography (PPG), the application of the Beer–Lambert law to biological tissues, and the optical absorption characteristics of oxygenated and deoxygenated hemoglobin at wavelengths of 660 nm and 940 nm. Furthermore, the article analyzes the operation of key hardware components, including dual-wavelength light-emitting diodes (LEDs), silicon photodiodes, transimpedance amplifiers, analog filters, analog-to-digital converters, and digital signal processing algorithms based on the ratio-of-ratios method for SpO₂ estimation. The review also discusses signal acquisition, conditioning, and calibration processes required to improve measurement accuracy under various physiological conditions. In addition, the study examines technical limitations and clinical challenges such as motion artifacts, peripheral hypoperfusion, dysfunctional hemoglobin, ambient light interference, and skin pigmentation bias that may affect measurement reliability. Recent technological developments are also reviewed, including multi-wavelength pulse oximetry, wearable reflectance photoplethysmography, flexible biosensors, and artificial intelligence-based signal processing techniques that enhance measurement robustness and clinical applicability. Overall, this review highlights the multidisciplinary nature of pulse oximeter technology and demonstrates how advances in biomedical physics, optical sensing, electronics, and intelligent signal processing continue to improve the performance, reliability, and future development of non-invasive physiological monitoring systems.